2020
DOI: 10.1097/scs.0000000000006991
|View full text |Cite
|
Sign up to set email alerts
|

Can the Bone Density Estimated by CBCT Predict the Primary Stability of Dental Implants? A New Measurement Protocol

Abstract: Background: The use of dental implants to restore edentulous parts of the jaws is a common and well-documented treatment method. Effective dental implant treatment is known to be affected by both the quality and the quantity of bone required for implant placement, bone quality is a critical factor to consider when predicting stability of implants. Thus, stability of the initial implant and the possibility of early loading could be predicated using cone-beam computed tomography (CBCT) scans and prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In our research, the grafting material was completely absorbable, so it was not affecting the measurements [50]. Moreover, numerous papers backing a correlation between CBCT-derived bone GVs and primary and secondary implant stability, which is a clinically significant parameter, were published [51][52][53][54][55]. Nevertheless, the literature data on those correlations are ambiguous, which has to be taken into consideration when drawing conclusions [50].…”
Section: Discussionmentioning
confidence: 79%
“…In our research, the grafting material was completely absorbable, so it was not affecting the measurements [50]. Moreover, numerous papers backing a correlation between CBCT-derived bone GVs and primary and secondary implant stability, which is a clinically significant parameter, were published [51][52][53][54][55]. Nevertheless, the literature data on those correlations are ambiguous, which has to be taken into consideration when drawing conclusions [50].…”
Section: Discussionmentioning
confidence: 79%
“…On the other hand, Degidi et al discovered a statistically negligible link between resonant frequency analysis results and mineralized bone–implant contact [ 38 ]. Also, a recent study conducted by Al Jamal and Al Jumaily in 2021 showed the use of CBCT to detect bone density is a reliable approach that is substantially connected with primary stability as measured by the implant stability meter [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, Al-Jamal et al [ 22 ] demonstrated that there was a significant correlation between primary stability and IT using the AnyCheck® device in the context of 40 implants. However, they did not compare their findings with measurements obtained using the Osstell® device.…”
Section: Discussionmentioning
confidence: 99%